2005
DOI: 10.1167/iovs.05-0843
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Lens Crystallins in an In Vivo Hyperbaric Oxygen Guinea Pig Model of Nuclear Cataract: Dynamic Light-Scattering and HPLC Analysis

Abstract: The results indicate that molecular oxygen in vivo can induce the cross-linking of guinea pig lens nuclear crystallins into large disulfide-bonded aggregates capable of scattering light. A similar process may be involved in the formation of human nuclear cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 68 publications
6
55
0
2
Order By: Relevance
“…As in our previous studies (Borchman et al, 2000;Simpanya et al, 2005), increased lens nuclear light scattering was also observed in the present study after 50 treatments of the guinea pigs with HBO, compared to age-matched controls, and the level of scatter intensified after 85 treatments. Since this type of slit-lamp data has been shown previously (Borchman et al, 2000;Simpanya et al, 2005), the results have not been repeated here.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As in our previous studies (Borchman et al, 2000;Simpanya et al, 2005), increased lens nuclear light scattering was also observed in the present study after 50 treatments of the guinea pigs with HBO, compared to age-matched controls, and the level of scatter intensified after 85 treatments. Since this type of slit-lamp data has been shown previously (Borchman et al, 2000;Simpanya et al, 2005), the results have not been repeated here.…”
Section: Resultssupporting
confidence: 92%
“…Age-matched control guinea pigs were included with each group of O 2 -treated animals. Both 50 and 85 HBO-treatments have been shown to produce an increased level of lens nuclear light scattering in guinea pigs, compared to age-matched controls (Borchman et al, 2000;Simpanya et al, 2005). A two-fold increase in lens focal length variability was observed after 70 treatments of guinea pigs with HBO (Bantseev et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidation of α-crystallin is linked to cataractogenesis, in particular oxidation of cysteine residues (Garner and Spector, 1980). Aggregation of lens crystallin has been demonstrated by Simpanya et al (2005) in guinea pigs treated with hyperbaric oxygen (higher than atmospheric oxygen tension) three times weekly for 7 months. In this study HPLC-isolated aggregates contained αA-but not αB-crystallin, which is devoid of -SH groups and thus does not participate in disulfide cross-linking.…”
Section: Mitochondrial Ros Systems and Cataractmentioning
confidence: 99%